PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP PERAN ORGANISASI KEMASYARAKATAN PEMUDA PANCASILA DI KOTA PEKANBARU - Ramadhani, Rico; Hambali, Hambali; Eddison, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study is entitled " The perception of Riau University students on the role of pemuda pancasila community organizations in pekanbaru city." The formulation of the problem in this study is how the University of Riau students perceive the Role of Pancasila Youth Community organizations in Pekanbaru City. The Role of Pancasila youth organizations in the city of Pekanbaru. The population of this study is all undergraduate students (S1) at the University of Riau. While the sample of this study was 150 respondents. Data collection techniques were interviews, questionnaires, library studies. Data analysis techniques using Quantitative Descriptive methods. The conclusion of this study is the percentage of excellent answers (SB) of 15.84% plus good answers (B) of 50.31% so that the results of 66.15% in the "Good" range, so that University of Riau Student Perceptions of the Role of Organizations The Pemuda Pancasila Community in Pekanbaru City is "Good".Key Words: Student Perceptions, Role, Organizations, Pemuda Pancasila